Micro-Variables of Dynamic Capabilities and How They Come into Effect – Exploring Firm-Specificity and Cross-Firm Commonalities - Wilkens, Uta; Sprafke, Nicole (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
This paper gives emphasis to four categories most relevant for microfoundations of dynamic ca-pabilities (DCs): (1) leadership behavior, (2) team interaction, (3) individual capabilities, and (4) job characteristics. We study whether micro-variables operate firm-specifically when constituting DCs and how they relate to one another. Data result from employee surveys (n = 486) conducted in five German organizations. The cross-firm comparison based on discriminant analyses reveals that micro-variables that constitute DCs often build firm-specific configurations in a broader set of variables. Only structural empowerment and team learning function as cross-firm commonali-ties. There is evidence to consider firm-specificity when explaining competitive advantages.